Myopia and orthokeratology for myopia control - Cho, Pauline; Tan, Qi (Clinical and experimental optometry, 2019)
The prevalence of myopia in children is increasing worldwide and is viewed as a major public health concern. This increase has driven interest in research into myopia prevention and control in children. Although there is still uncertainty in the risk factors underlying differences in myopia prevalence between ethnic groups, rates in children of East Asian descent are typically higher regardless of where they live. Mounting evidence also suggests that myopia prevalence in children increases with age. Earlier commencement and more rigorous education systems in these countries, resulting in more time spent on near-work activities and less time on outdoor activities, may be responsible for the earlier age of myopia onset. However, to date, the mechanisms regulating myopia onset and progression are still poorly understood. Findings from several studies have shown orthokeratology to be effective in slowing axial elongation and it is a well-accepted treatment, particularly in East Asian regions. While our understanding of this treatment has increased in the last decade, more work is required to answer questions, including: How long should the treatment be continued? Is there a rebound effect? Should the amount of myopia control be increased? To whom and when should the treatment be offered? Practitioners are now faced with the need to carefully guide and advise parents on whether and when to undertake a long somewhat complex intervention, which is costly, both in time and money. In the near future, a greater demand for effective prophylaxis against childhood myopia is envisaged. Other than orthokeratology, atropine therapy has been shown to be effective in slowing myopia progression. While its mechanism of control is also not fully understood, it is likely that it acts via a different mechanism from orthokeratology. Thus, a combined treatment of orthokeratology and atropine may have great potential to maximise the effectiveness of myopia control interventions.